Acute flaccid paralysis indicators during the COVID-19 pandemic in Mozambique 2019 - 2020 - Beatriz Nhantumbo; Dionísia Balate; Samuel Nuvunga; Fabião Maússe; Eduardo Chicanequisso; Neusa Fataha; Cidia Francisco; Áuria Banze; Judite Monteiro; Erika Rossetto; Cynthia Baltazar (Journal of Interventional Epidemiology and Public Health)
Introduction: During the state of emergency posed by the COVID-19 pandemic, one of the primary communications for the public health control and prevention measures was "stay at home". However, what happens to the indicators of diseases aimed at eradication when people stay at home? We aimed to evaluate the Acute Flaccid Paralysis (AFP) surveillance indicators and determine the polio vaccine coverage in Mozambique, 2019-2020.